No change in energy systems power rate production constants over a competitive swimming season - Novitsky, S. A. (Medicine & Science in Sports & Exercise, 1998)
The aerobic and anaerobic energy systems' power rate production constants were studied over a competitive season. Female collegiate swimmers (N = 15) performed three maximal tethered swims (10-s, 30-2, and 90-s) on three occasions during a collegiate swimming season. Total work for each of the duration-trials or the power rate productions for each energy system did not change significantly over the season. The author attempted to assert that the changes observed were of practical significance. However, the study showed that any observed changes were no better than those that would be expected by chance alone (given the small F values and the low probability estimates). Implication. In collegiate female swimmers, changes in either aerobic or anaerobic energy production do not occur over a season of swimming. This supports the contention that when growth has ceased in trained athletes, no further changes in capacity of the energy systems occur.